Mobile Application Development for Optimizing Management Information Systems - Nurrizqa (Journal Informatic, Education and Management (JIEM), 2023)
The development of Mobile Applications for Optimization of Management Information Systems is an important innovation in the context of enhancing efficiency and effectiveness of organizational management. The objective of this research is to design and implement a mobile application that can optimize the information management process within a management system. Research methods used include user needs surveys, system requirements analysis, application design, prototype development, as well as testing and evaluation by users. The research results indicate that the developed mobile application is able to improve information accessibility, accelerate decision-making processes, and enhance work efficiency. Based on the data analysis conducted, the conclusion of this research is that the implementation of mobile applications in management information systems can significantly enhance organizational performance. This research provides a significant contribution in the context of user-oriented information technology development and improving organizational operational efficiency.